2014
DOI: 10.1371/journal.pone.0096819
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Comprehensive Stroke Care Capabilities on In-Hospital Mortality of Patients with Ischemic and Hemorrhagic Stroke: J-ASPECT Study

Abstract: BackgroundThe effectiveness of comprehensive stroke center (CSC) capabilities on stroke mortality remains uncertain. We performed a nationwide study to examine whether CSC capabilities influenced in-hospital mortality of patients with ischemic and hemorrhagic stroke.Methods and ResultsOf the 1,369 certified training institutions in Japan, 749 hospitals responded to a questionnaire survey regarding CSC capabilities that queried the availability of personnel, diagnostic techniques, specific expertise, infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 23 publications
4
96
2
Order By: Relevance
“…27 The present study is the first to compare outcomes for SAH patients treated with clipping and coiling via a mixed-model analysis of a large nationwide discharge database (DPC database) after adjustment for patient-level characteristics including age, sex, level of consciousness (JCS score), CCI score, and hospital-level CSC capabilities (CSC score). 14,15 Our results revealed that patients who had undergone coiling exhibited significantly higher in-hospital mortality (12.4% vs 8.7%) and shorter hospital stays (32.0 vs 37.0 days) than those in patients who had undergone clipping. The proportion of patients discharged with mRS scores of 3-6 (coiling 46.4%, clipping 42.9%) and median medical costs (thousands US$: coiling 35.7, clipping 36.7) were not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…27 The present study is the first to compare outcomes for SAH patients treated with clipping and coiling via a mixed-model analysis of a large nationwide discharge database (DPC database) after adjustment for patient-level characteristics including age, sex, level of consciousness (JCS score), CCI score, and hospital-level CSC capabilities (CSC score). 14,15 Our results revealed that patients who had undergone coiling exhibited significantly higher in-hospital mortality (12.4% vs 8.7%) and shorter hospital stays (32.0 vs 37.0 days) than those in patients who had undergone clipping. The proportion of patients discharged with mRS scores of 3-6 (coiling 46.4%, clipping 42.9%) and median medical costs (thousands US$: coiling 35.7, clipping 36.7) were not significantly different between the groups.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, international, national, and longitudinal comparisons of outcomes for patients with SAH treated using different therapeutic modalities should be discussed in light of socioeconomic indicators, acute stroke care capabilities at the specific time, 13,14,26,28,31 and patient-level characteristics such as SAH severity. 27 The present study is the first to compare outcomes for SAH patients treated with clipping and coiling via a mixed-model analysis of a large nationwide discharge database (DPC database) after adjustment for patient-level characteristics including age, sex, level of consciousness (JCS score), CCI score, and hospital-level CSC capabilities (CSC score).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations